Shell thickness determination for PTFE‐PS core‐shell nanoparticles using scanning transmission X‐ray microscopy (STXM). (10th May 2018) - Müller, A.; Swaraj, S.; Sparnacci, K.; Unger, W.E.S.
Abstract : A scanning transmission X‐ray microscopy (STXM)‐based methodology is introduced for determining the dimensions (shell thickness, core and total diameter) of core‐shell nanoparticles, which exhibit a strong X‐ray absorption contrast and a well‐defined interface between core and shell material. A low radiation dosage during data acquisition and, therefore, less X‐ray beam‐induced damage of the sample is achieved by recording STXM images only at 2 predetermined energies of maximum absorption contrast, instead of recording a stack of images across the whole absorption edge. A model core‐shell nanoparticle, polytetrafluoroethylene (PTFE) cores with polystyrene (PS) shell, is used for demonstration. Near‐edge X‐ray absorption fine structure spectroscopy confirms the significant difference in X‐ray absorption behavior between PTFE and PS. Additionally, because of the insolubility of styrene in PTFE a well‐defined interface between particle core and shell is expected. To validate the STXM results, both the naked PTFE cores as well as the complete core‐shell nanoparticles are examined by scanning electron microscopy (SEM). The introduced STXM‐based methodology yields particle dimensions in agreement with the SEM results and provides additional information such as the position of the particle core, which cannot be extracted from a SEM micrograph.